The panda puzzle - Roy, Ron; Gurney, John Steven (New York : Random House, 2002)
Dink, Josh, and Ruth Rose investigate the kidnapping of the new baby panda at the petting zoo.
"A stepping stone book."
Keywords: Giant panda; Pandas; Zoos; Mystery and detective stories